2020
DOI: 10.1016/j.puhe.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of social distancing on the compound growth rate of COVID-19 at the county level (United States) using statistical analyses and a random forest machine learning model

Abstract: Objectives: The goal of the present work is to investigate trends among US counties and coronavirus disease 2019 growth rates in relation to the existence of shelter-in-place (SIP) orders in that county.Study design: This is a prospective cohort study. Methods: Compound growth rates were calculated using cumulative confirmed COVID-19 cases from January 21, 2020, to March 31, 2020, in all 3139 US counties. Compound growth was chosen as it gives a single number that can be used in machine learning to represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 5 publications
2
40
0
5
Order By: Relevance
“…Epidemiological, statistical and mathematical models have also been introduced to predict the distribution, to observe the changes depending on meteorological conditions, and to examine the structure of this epidemic which affects all countries globally [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Besides, the performance of machine learning approaches for the diagnosis and treatment of the disease was also studied [22] , [23] , [24] , [25] , [26] , [27] , [28] . All these studies reveal the general structure of such an epidemic and disease that humanity has not encountered before and its effects on society.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological, statistical and mathematical models have also been introduced to predict the distribution, to observe the changes depending on meteorological conditions, and to examine the structure of this epidemic which affects all countries globally [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Besides, the performance of machine learning approaches for the diagnosis and treatment of the disease was also studied [22] , [23] , [24] , [25] , [26] , [27] , [28] . All these studies reveal the general structure of such an epidemic and disease that humanity has not encountered before and its effects on society.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus 2 (CoV-2) is a new beta-coronavirus related to severe acute respiratory syndrome (SARS) that emerged in December 2019 in China and became a pandemic in March 2020 due to its high infection and mortality rates (1)(2)(3). COVID-19 was the official name given to the disease caused by the new coronavirus of 2019 (SARS-CoV-2) by the World Health Organization (WHO) (1).…”
Section: Introductionmentioning
confidence: 99%
“…They have used statistical analysis and random forest approach to analyze the cumulative growth trend of COVID-19. They have concluded that the growth trend of COVID-19 is effectively reduced after SIP order of US government and countries with higher density getting more benefit from the SIP order [3].…”
Section: Related Workmentioning
confidence: 99%